Clinico-Histological Features of Thrombotic Microangiopathy in Renal Biopsies: A Retrospective Study - Niraimathi MANICKAM; Vinita AGRAWAL; Pallavi PRASAD; Manoj JAIN; Narayan PRASAD (Federation of Turkish Pathology Societies, 2022)
Objective: Thrombotic microangiopathy (TMA) is often first detected on a renal biopsy performed for renal manifestations. Apart from hemolytic uremic syndrome (HUS) and thrombotic thrombocytopenic purpura, there are various secondary conditions associated with TMA. This study analyzes the clinico-pathological spectrum, etiological factors and renal outcome of TMA diagnosed on renal biopsy. Material and Method: A retrospective evaluation of renal biopsies for TMA over 5.5 years was performed. Clinical and laboratory data was collected from patient records. Results: A total of 40 biopsies from 39 patients showed TMA comprising 33 native and 7 transplant biopsies. Malignant hypertension (n=13) was the most common etiology in native biopsies followed by postpartum TMA (n=7), atypical HUS (aHUS) (n=7), and lupus nephritis (n=6). TMA in transplant biopsies was due to acute rejection (n=4) and CNI toxicity (n=3). Serum creatinine was high in most patients (mean 5.6 + 2.5 mg/ dl). aHUS showed the highest mean LDH levels and the lowest average platelet counts. Renal biopsies in malignant hypertension and postpartum TMA showed isolated arterial changes while aHUS and lupus nephritis showed both glomerular and arterial involvement. Postpartum TMA and aHUS had poor renal outcome requiring renal replacement therapy. Conclusion: Most postpartum TMA and aHUS had systemic features of TMA while malignant hypertension and lupus nephritis showed 'isolated renal TMA'. This emphasizes the importance of careful evaluation of renal biopsies even in the absence of systemic features of TMA.